Effect of different speed and time of centrifugations on decontamination of Leptospira spp. cultures from rat’s kidney - Budi Prasetyo; Arif Mulyanto; Kusnanto Mukti Wibowo; Kurniawan; Farida Dwi Handayani (Jurnal Teknologi Laboratorium)
The centrifugal force in the centrifuge is able to change the surface properties of bacterial cells and the inner structure, including DNA, so that it can damage bacterial cells. The pathogenic bacterium Leptospira spp is a zoonosis that lives in the kidneys of rats as a natural reservoir, but breeding it is still a challenge because it can be contaminated with other bacteria. Decontamination methods are needed to obtain clean and pure Leptospira spp cultures for further examination and epidemiology. This study aims to obtain an appropriate decontamination method for the sustainability of Leptospira spp cultures in the laboratory using a combination of centrifugation speeds. Leptospira spp cultures were obtained from leptospirosis endemic areas in Central Java Province, Demak Regency, Gebang Village and Tridonorejo as many as 13 Leptospira spp cultures contaminated with cocci, coma, and filaments. Cultures were observed at 20x magnification under a dark field microscope at 8 weeks old. Contaminated cultures were centrifuged at 3000, 6000, and 8000 rpm for 5 and 10 minutes, then recultured into new media. The media used in this study were EMJH + STAFF and V5FU media. The results showed that rat kidney cultures showed 7 and 6 positives from the Gebang and Tridonorejo areas. Data on the results of bacterial decontamination obtained at a speed of 3000 rpm for 5 minutes has a greater percentage than the speed of 6000 and 8000 rpm with a result of 30.8%. This is in the process of purifying Leptospira spp using centrifugation proven to remove contaminant bacteria such as cocci, coma, and filaments. This is because centrifugation speed is able to change the nature of the surface structure and interior of bacterial cells, including DNA, so that it can damage bacterial cells.